Where semantics meets pragmatics - Heusinger, Klaus von; Turner, Ken, 1956- (Current research in the semantics/pragmatics interface, 2006)
Integrates semantic and pragmatic facts into a single theory, and attempts to design and corroborate an account of meaning and use that would be compatible with other aspects of human behaviour. This reference is useful for scholars and students interested in the vibrant discipline of semantics-pragmatics.